2014
DOI: 10.1103/physrevc.90.011303
|View full text |Cite
|
Sign up to set email alerts
|

Toward extremes of angular momentum: Application of the Pfaffian algorithm in realistic calculations

Abstract: In a calculation of rotated matrix elements with angular momentum projection, the generalized Wick's theorem may encounter a practical problem of combinatorial complexity when the configurations have more than four quasi-particles (qps). The problem can be solved by employing the Pfaffian algorithm generally applicable to calculations of matrix elements for Hartree-Fock-Bogoliubov states with any number of qps. This breakthrough in many-body techniques enables studies of high-spin states in a shell-model frame… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
0
37
2
Order By: Relevance
“…Also, shape fluctuations can strongly affect K mixing and hence the decay properties of states [28]. The projected shell model (PSM) [18,19], as a calculation truncated in an angularmomentum-projected basis with qp configurations [29], is suitable for studying the behaviors of different qp states and mixing among them. However, the existing PSM applies to deformation-fixed calculations, i.e., assuming a fixed deformation in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, shape fluctuations can strongly affect K mixing and hence the decay properties of states [28]. The projected shell model (PSM) [18,19], as a calculation truncated in an angularmomentum-projected basis with qp configurations [29], is suitable for studying the behaviors of different qp states and mixing among them. However, the existing PSM applies to deformation-fixed calculations, i.e., assuming a fixed deformation in calculations.…”
Section: Introductionmentioning
confidence: 99%
“…For efficiency, we use the new techniques of Refs. [19][20][21] to evaluate the kernels for projections.…”
Section: Introductionmentioning
confidence: 99%
“…The Nilsson-BCS calculation defines a deformed qp basis from which the PSM model space is constructed. The multi-qp configurations up to 6-qp states for even-even nuclei are given as [18] …”
Section: Application Of the Pfaffian Algorithm 21 The Formalismmentioning
confidence: 99%
“…Moreover, it has been shown that the Pfaffian algorithm is very efficient also for calculating overlap matrix elements [11][12][13][14][15][16]. In particular, by means of Fermion coherent states and the Grassmann integral, one can derive an alternative approach to calculate the rotated matrix element for general qp states [17], which serves as a theoretical framework to extend the PSM model space [18].…”
Section: Introductionmentioning
confidence: 99%